Fenomena Kepemimpinan Karismatis di Era Transisi Menuju Demokrasi Pasca Reformasi - Budhy Prianto (Universitas Sebelas Maret, 2023)
Although Max Weber's three typologies of authority, namely traditional authority, charismatic authority, and rational-legal authority have been classified as a classical theory, they are still considered relevant and referred to by academics for various scientific purposes. Also in daily socio-political practices in Indonesian society today, the phenomenon of life can be found in three typologies of authority. Simultaneously, the three typologies of authority can be found at the community level, state level, and in the relationship between society and the state. However, in the current era of democratic governance, the use and acceptance of these three types of authority cannot be avoided from criticism and controversy, especially those related to charismatic authority. There is a tendency for the development –or redevelopment – of charismatic leadership to be felt in recent years. Many leaders and figures who feel that they are leaders deliberately equip themselves with a mythical aura, or mystical, in order to boost their personal charismatic authority, in order to legitimize their power and influence. By using literature research and content analysis, this paper tries to find answers on how to manage the tendency of charismatic leadership types to be in line with democratic governance values that are currently being developed. The results of the study show that there are two ways to synergize charismatic authority with demands for democratic governance. On the one hand, carry out the process of demystifying charisma, and on the other hand, continue to encourage the development of procedural and substantial democratic values.